Changes Unseen in A Century: Changes in Concepts of Governance and China’s Responses - Qiyu Zhang (Law and Economy, 2024)
Today’s world is in a situation of “Changes Unseen in A Century”. Wu Yujin’s holistic view of world history reveals the overall development law of world history, and provides ideas for the study of changes in the concept of global governance. In the face of the “Changes”, China should, on the one hand, actively participate in global governance, continuously promote the building of a community of human destiny, respect the consensus of the international community, and enhance its ability to participate in and formulate the rules of global governance; and on the other hand, emphasize the shaping of its soft power to enhance its own governance capacity.